Risk factors and prognosis of liver metastasis in gallbladder cancer patients: A SEER-based study - Fang, Cheng; Li, Wenhui; Wang, Qingqiang; Wang, Ruoran; Dong, Hui; Chen, Junjie; Chen, Yong (Frontiers in Surgery, 2022)
Background: Liver metastasis is commonly complicated in gallbladder cancer (GBC). We design this study to develop model for predicting development of liver metastasis in GBC patients and evaluate the risk of mortality in these patients with liver metastasis. Methods: GBC patients from Surveillance Epidemiology and End Results (SEER) between 2010-2016 were included for this study. Logistic regression was performed to discover risk factors and construct predictive model for liver metastasis in GBC patients. Cox regression was utilized to find risk factors of mortality in GBC patients with liver metastasis. Area under the receiver operating characteristic curve (AUC) was calculated to evaluate the performance of constructed predictive models. Results: Multivariate logistic regression confirmed T stage, N stage and tumor grade were risk factors of the liver metastasis in GBC patients. Composed of these factors, the model for predicting development of liver metastasis had AUCs of 0.707 and 0.657 in training cohort and testing cohort, respectively. Multivariate cox regression showed surgery of primary site and chemotherapy were independently associated with mortality of GBC patients with liver metastasis. Composed of these two factors, the predictive model for 1-year mortality of GBC patients with liver metastasis had AUCs of 0.734 and 0.776 in training cohort and testing cohort, respectively. Conclusion: Predictive models we constructed are helpful for surgeons to evaluate the risk of liver metastasis in GBC patients and the survival condition of those with liver metastasis. Surgery of primary site and chemotherapy should be provided for GBC with liver metastasis.